2015
DOI: 10.1088/0031-9155/60/23/8923
|View full text |Cite|
|
Sign up to set email alerts
|

Short-lived positron emitters in beam-on PET imaging during proton therapy

Abstract: The only method for in vivo dose delivery verification in proton beam radiotherapy in clinical use today is positron emission tomography (PET) of the positron emitters produced in the patient during irradiation. PET imaging while the beam is on (so called beam-on PET) is an attractive option, providing the largest number of counts, the least biological washout and the fastest feedback. In this implementation, all nuclides, independent of their half-life, will contribute. As a first step towards assessing the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 46 publications
(69 reference statements)
1
53
0
Order By: Relevance
“…As it is clear from the figures, the best fit function includes the contributions of 11 C, 15 O, 10 C, 8 B where, as expected, the fist two isotopes are the most abundant ones. The presence of these 4 isotopes is also reported in other experiments where 55 MeV protons impinging on a PMMA phantom and an ad-hoc experimental setup for time analysis are used [27]. From Fig.…”
Section: Temporal Profilessupporting
confidence: 67%
“…As it is clear from the figures, the best fit function includes the contributions of 11 C, 15 O, 10 C, 8 B where, as expected, the fist two isotopes are the most abundant ones. The presence of these 4 isotopes is also reported in other experiments where 55 MeV protons impinging on a PMMA phantom and an ad-hoc experimental setup for time analysis are used [27]. From Fig.…”
Section: Temporal Profilessupporting
confidence: 67%
“…As can be observed, the d value for the in-spill data is comparable with the interspill one within 0.4 mm. The lower value of the slope for the in-spill profile can be explained by the contribution of the long positron range of short-lived βþ emitters, 45,46 such as 12 N, and the contributions of prompt photons. 16 In the following part, we report on the results obtained for the second set of measurements with the PMMA phantoms A and B.…”
Section: Results Of the Measurements With The Polymethyl Methacrylatementioning
confidence: 99%
“…Protons of 55 MeV, hitting of PMMA target, were first simulated. The goal was to compare the Geant4 predictions to the experimental results obtained by Dendooven et al [15], reported in the table I. The relative difference between Geant4 and the experimental results are shown on figure 12, for the Binary Cascade (BIC) and the BIC High Precision (BIC AllHP) models.…”
Section: Monte-carlo Simulationmentioning
confidence: 97%